2006
DOI: 10.1200/jco.2006.24.18_suppl.10615
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of trastuzumab (H) + capecitabine (X) as first-line treatment in patients (pts) with HER2-positive metastatic breast cancer (MBC)

Abstract: 10615 Background: The addition of H to a taxane provides significant clinical benefit, including prolonged survival, in HER2-positive MBC. H adds little to the toxicity of taxanes alone. As monotherapy, X has consistently high activity and favorable safety. The addition of X to docetaxel extends survival in MBC. Preliminary data [Bangemann et al. 2000] indicated that the combination of H + X is effective and well-tolerated for intensively pretreated HER2-positive MBC (ORR 47%). The current study evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Diarrhea, HFS, and nausea were the most common AEs across both treatment groups. The high clinical activity of trastuzumab plus capecitabine combination therapy was also reported in three singlearm, phase II studies as first-line (n ϭ 63) and later lines of treatment (n ϭ 74) in HER-2-positive MBC patients [16,17,28]. In the first-line setting, ORRs were Ͼ60%, with a median TTP of 9.2 months and median OS time of 25.6 months [16,17].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Diarrhea, HFS, and nausea were the most common AEs across both treatment groups. The high clinical activity of trastuzumab plus capecitabine combination therapy was also reported in three singlearm, phase II studies as first-line (n ϭ 63) and later lines of treatment (n ϭ 74) in HER-2-positive MBC patients [16,17,28]. In the first-line setting, ORRs were Ͼ60%, with a median TTP of 9.2 months and median OS time of 25.6 months [16,17].…”
Section: Discussionmentioning
confidence: 64%
“…The high clinical activity of trastuzumab plus capecitabine combination therapy was also reported in three singlearm, phase II studies as first-line (n ϭ 63) and later lines of treatment (n ϭ 74) in HER-2-positive MBC patients [16,17,28]. In the first-line setting, ORRs were Ͼ60%, with a median TTP of 9.2 months and median OS time of 25.6 months [16,17]. A number of clinical trials have demonstrated the efficacy of doublet combinations of trastuzumab, bevacizumab, and capecitabine in patients with MBC [11,[15][16][17].…”
Section: Discussionmentioning
confidence: 66%
“…In the firstline setting, the overall response rate was 73%, including a 15% complete response rate. An additional eight patients (20%) had stable disease, leading to a clinical benefit in 93% of patients [3]. The only grade 3 adverse events were hand-foot syndrome in four patients and leukopenia in one patient, but both resolved with dose interruption or reduction.…”
Section: Further Options With Capecitabine-containing Combinationsmentioning
confidence: 98%
“…Capecitabine-based therapy has also been evaluated in HER-2-positive MBC, and the first phase III trial will report in 2006. Capecitabine plus trastuzumab has shown high first-line activity [3] and is also highly active in patients with pretreated disease [63,64]. In the firstline setting, the overall response rate was 73%, including a 15% complete response rate.…”
Section: Further Options With Capecitabine-containing Combinationsmentioning
confidence: 99%
See 1 more Smart Citation